High-flow arteriovenous fistula in X-linked Alport syndrome: a case report - Takahashi, Daisuke; Katayama, Kan; Iyoda, Yoshinobu; Fukumori, Ayumi; Tsujimoto, Kayo; Yamawaki, Masahiro; Tanaka, Fumika; Saiki, Ryosuke; Oda, Keiko; Suzuki, Yasuo; Murata, Tomohiro; Okugawa, Yoshinaga; et al. (Frontiers in Medicine, 2023)
Most male X-linked Alport syndrome patients with COL4A5 nonsense mutations experience end-stage kidney failure by 30 years old. Although there is no definition of high-flow arteriovenous fistula, access blood flows greater than 2000 mL/min might predict the occurrence of high-output heart failure. A 50-year-old Japanese man had suffered from proteinuria at 4 years old and sensorineural hearing loss and a lenticular lens at 20 years old.He had started to receive hemodialysis treatment due to end-stage kidney disease at 22 years old. A genetic test confirmed a novel hemizygous nonsense variant COL4A5 c.2980G>T (p. Gly994Ter), and he was diagnosed with X-linked Alport syndrome. COL4A5 c.2980G>T was considered "pathogenic" according to the American College of Medical Genetics and Genomics guidelines and in vitro experiments. Shortness of breath on exertion was exaggerated, his brachial artery blood flow was over 4236-4353 ml/min, his cardiac output was 5874 ml/min, and he needed radial artery banding at 51 years old. After radial artery banding surgery, the brachial artery blood flow decreased to 987-1236 ml/min, and echocardiography showed a cardiac output at 5100 ml/min with improved E' and E/E'. His shortness of breath on exertion improved gradually. Although rare, high-output heart failure due to high-flow arteriovenous fistula should be kept in mind as a complication in X-linked Alport syndrome patients, and our patient was successfully treated with radial artery banding surgery.